Considering the Existence of Academic Draft as the Political Instrument of Law Development - Herry Wiyanto (Unnes Law Journal, 2021)
The direction of law development follows the nation's ideas or goals, which is the formulation to achieve the state's goal as contained in the Preamble of the 1945 Constitution of the Republic of Indonesia, which is to protect protect the whole people of Indonesia and the entire homeland of Indonesia, and in order to advance general prosperity, to develop the nation's intellectual life, and to contribute to the implementation of a world order based on freedom, lasting peace and social justice. This paper answers some problems, including How is the essence of academic draft in making laws and regulations in Indonesia, To what extent is academic draft's contribution as an instrument of the national development and how is the ideal concept of academic draft as the instrument of instrument the national development. The essence of academic draft is the philosophical, sociological and juridical bases of a draft of law and regulation and the assessment and harmonization function and the existence of academic draft are designed as the catalyst of a product of legislation to be made so as not to be out of the appropriate principles. Academic draft's contribution to the current national law development is felt lacking because of the newly required bill making process after 2011 through Law 12 Year 2011 concerning Formation of Laws and Regulations. Besides, academic draft is not yet capable of harmonizing and balancing every interest group in every bill discussion. In the ideal concept, the role of academic draft as the assessment and harmonization in every Bill is capable of preventing overlapping regulation or interest out of the law intervening Bill making for the regulation to remain in the real law corridor. It also needs regulatory arrangement by academic draft arranging team to maintain the objectivity.